TECHNICAL ASPECTS AND ECONOMIC BENEFITS OF THE JUVENILE CRAB NURSERY IN LINING TANK IN NAM CAN DISTRICT, CA MAU PROVINCE - Viet, Le Quoc; Hai, Tran Ngoc; Phuong, Nguyen Thanh (Vietnam Journal of Marine Science and Technology, 2015)
Study on technical aspects and economic benefits of the juvenile crab nursery in lining ponds/tanks in Nam Can district, Ca Mau province was conducted from August to December 2014. Thirty five farmers were interviewed in Ham Rong commune, Nam Can district, Ca Mau province. The results showed that the average area of the lining tanks was 9.6 m2; with 0.3 m in depth and 100% net substrates. Stocking density was 256.7 inds/m2. 40% of farmers used fresh krill (sergestidae) as feed and 60% of farmers combined fresh krill (sergestidae) and pellet feed. Survival rate reached 84.9% and the average productivity was up to 237.4 inds/m2. The total production was 986,000 inds/year/farmer. The total production cost was 18.8 million VND/production run; the income was 5.1 million VND/run (121 million VND/year/farmer) and 94% of farmers made profit. The study also determined factors affecting the efficiency of the rearing model including (i) nursery area; (i) megalops price; (iii) stocking density; (iv) survival rate and (v) selling price.